United Republic of Tanzania : Water Resources Assistance Strategy - World Bank (World Bank, Washington, DC, 2016)
In the past decade, Tanzania has experienced high economic growth and it is in the global limelight as a recent success story in Africa. A variety of factors have contributed to this success, including liberalized policies and reforms, infusion of external capital from development partners and the private sector, debt cancellation, and a strong performance by emerging sectors such as mining, tourism, and fisheries. Its social policies, largely influenced by the First President Julius Kambarage Nyerere, including a single national language and relative political stability have contributed to a strong sense of nationhood, which sets it apart from many of its neighbors and has provided an unusual degree of stability that has facilitated major economic transformation without a significant social backlash.